Risk of cancer development associated with disease-modifying therapies for multiple sclerosis: study protocol for a systematic review and meta-analysis of randomised and non-randomised studies - Catalá-López, Ferrán; Tejedor-Romero, Laura; Driver, Jane A.; Hutton, Brian; Sánchez-Ortí, Joan V.; Ridao, Manuel; Alonso-Arroyo, Adolfo; Correa-Ghisays, Patricia; Forés-Martos, Jaume; Balanzá-Martínez, Vicent; Valencia, Alfonso; Cobos, Inmaculada; et al. (Université d'Ottawa | University of Ottawa, 2024)
Abstract Background The association between cancer and multiple sclerosis has long been investigated. Several studies and reviews have examined the risk of cancer among patients with multiple sclerosis treated with disease-modifying therapies (DMTs) but with conflicting results. This study will aim to investigate the association between DMTs for multiple sclerosis and subsequent cancer risk using research synthesis methods. Methods/design We designed and registered a study protocol for a systematic review and meta-analysis. We will include randomised and non-randomised trials, prospective or retrospective cohort studies, and case–control studies of treatment with DMTs compared with placebo, no treatment, or another active agent. The primary outcome will be the risk of cancer (all-malignant neoplasms) in association with the exposure of DMTs. Secondary outcomes will include site-specific cancers (e.g. breast cancer). Literature searches will be conducted in multiple electronic databases (from their inception onwards), including the following: PubMed/MEDLINE, EMBASE, and Cochrane Central Register of Controlled Trials (CENTRAL). Two researchers will screen all citations, full-text articles, and abstract data independently. The risk of bias (quality) of individual studies will be appraised using an appropriate tool. If feasible, we will use a two-stage approach to evidence synthesis: (1) Peto’s method for meta-analysis of data from randomised trials alone; and (2) Random-effects model for meta-analysis adding data from non-randomised studies. We will calculate odds ratios and their associated 95% confidence intervals. Potential sources of heterogeneity will be explored in additional analyses (e.g. subgroups considering different DMTs individually, mechanism of action, type of control, length of follow-up, mode of treatment). Discussion This systematic review and meta-analysis of randomised and non-randomised studies will provide an updated synthesis of the risk of cancer associated with DMTs for adult patients with multiple sclerosis. This study will also examine some factors that may explain potential variations across studies. The findings will be published in a peer-reviewed journal. Systematic review registration Open Science Framework ( https://osf.io/v4sez ).